The EU Charter of Fundamental Rights : an originalist analysis - Brittain, Stephen (Trinity College (Dublin, Ireland). School of Law, 2015)
This thesis is about the method by which a novel and unusual form of law ought to be interpreted. That law is the European Charter of Fundamental Rights (CFR), which was drafted in 2000 and first given legal effect in 2009. The CFR sets out a comprehensive range of fundamental rights, ranging from traditional civil and political rights such as the right to freedom of expression (art 11) to novel forms of social and economic rights such as the right to collective bargaining (art 28).
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin.